Development And Analysis Of Rotordynamics System - Hayzir, Mohammad Ikhmal Fitri Mohd (Universiti Sains Malaysia, 2021)
A major factor to consider for achieving the optimal configuration of response characteristics and service performance is the dynamic behaviour of the rotor system. Determination of the natural frequencies of the structure, the mode shapes to reinforce the most flexible regions or locate the ideal locations where the mass should be reduced or damping should be enhanced, and the damping factors to avoid large vibrations. Oil whirl is a problem that occurs when journal bearings are implemented on machines that also have pressure lubrication systems and occur at high speeds. This research is to study the fluid-induced instability phenomenon in the journal bearing system. A static deflection and simulation of modal analysis are carried out using ANSYS software to determine the critical speed of the system. The mode shape of the system of the damped system in the ANSYS software to study the bearing behaviour at different operating speeds. In this research shows the oil whirl and oil whip phenomenon are determined in the damped modal analysis is at 550.9 rpm and 2000 rpm respectively. The mode shape of the rotating shaft also able to identify using the damped modal analysis. From that result, the critical speed of the rotating shaft is 1101 rpm, and the mode shape during the critical speed is under the cylindrical mode type.